Arah Gerakan Mahasiswa: Gerakan Politik Ataukah Gerakan Moral? - Sunyoto Usman (Jurnal Ilmu Sosial dan Ilmu Politik, 1999)
As a politically-active segment of the society, university students take part in shaping how political system works. Historical tracing of student movement during the post-independent period offered in this article provides an empirical and contextual basis for the student to decide, whether the movement is constructed as political movement or moral movement.